2019
DOI: 10.1038/s41419-019-1850-4
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA ABHD11-AS1 functions as a competing endogenous RNA to regulate papillary thyroid cancer progression by miR-199a-5p/SLC1A5 axis

Abstract: With the increasing incidence of papillary thyroid cancer (PTC), more attention has been paid to exploring the mechanism of PTC initiation and progression. In addition, ectopic expression of long noncoding RNAs (lncRNAs) is reported to play a pivotal role in multiple human cancers. Based on these findings, we examined lncRNA ABHD11 antisense RNA 1 (ABHD11-AS1) expression and its clinical significance, biological function and mechanism in PTC. First, we analyzed thyroid ABHD11-AS1 expression in The Cancer Genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 36 publications
1
61
0
Order By: Relevance
“…Long non-coding RNA (LncRNA) FYVE, RhoGEF and PH domain containing 5 antisense RNA 1 (FGD5-AS1) has been reported as oncogene in colorectal cancer, promoting its tumorigenesis [16]. Mechanistically, lncRNAs can exert functions in human cancers by sequestering miRNAs to up-regulate downstream protein-coding mRNAs [17][18][19]. According to previous study, we can speculate that FGD5-AS1 has its critical role in tumor progression, and we found that it can sponge to miR-107 in our assays.…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNA (LncRNA) FYVE, RhoGEF and PH domain containing 5 antisense RNA 1 (FGD5-AS1) has been reported as oncogene in colorectal cancer, promoting its tumorigenesis [16]. Mechanistically, lncRNAs can exert functions in human cancers by sequestering miRNAs to up-regulate downstream protein-coding mRNAs [17][18][19]. According to previous study, we can speculate that FGD5-AS1 has its critical role in tumor progression, and we found that it can sponge to miR-107 in our assays.…”
Section: Introductionmentioning
confidence: 99%
“…Histological types of TC include papillary carcinoma (PTC), follicular carcinoma (FTC), anaplastic carcinoma (ATC)/undifferentiated carcinoma, and medullary carcinoma (MTC) [4], and there have been different mutational profiles in these subtypes. Recent studies have confirmed a few molecular markers that have allowed better understanding of the molecular mechanisms of TC, for instance, BRAF and RAS point mutations, RET/PTC and PAX8/PPAR gene rearrangements, and so on [5][6][7]. Targeting certain molecules associated with initiation and progression of TC will be a significant and promising research area.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, the incidence of thyroid cancer is ascending, which may be attributed to the improvement of the early diagnosis of thyroid cancer [4]. Although the therapeutic strategies, including thyroidectomy, radioiodine therapy and thyroid-stimulating hormone inhibition therapy, have greatly improved the survival quality of early thyroid cancer patients, the prognosis of advanced and metastatic patients is dissatisfactory [5]. Therefore, it is very meaningful to investigate the underlying molecular mechanism for providing the meritorious therapeutic protocol of thyroid cancer patients.…”
Section: Introductionmentioning
confidence: 99%